Agricultural growth, rural development and poverty - Parthasarathy, G. (Visakhapatnam, 1988)
The volume contains writings of Prof. Parthasarathy over the last three decades on a theme close to his heart, Agricul tural Growth, Rural Development and Poverty'. Altogether there are 23 articles presented under eight sub-themes in this book. And, it contains the for word by Prof. M... Dantwala, the doyen among the agricultural economists in India, besides a comprehensive list of Prof. Pa. sarathy's re earch contri butions and the positions held and awards received by him over the years.
Keywords: Rural development-India